Coletivo Uttopia21: um estudo a respeito das mutações dos corpos cibernéticos - Silva, Dayse Alvares de Morais (2014)
The research aims to analyze the formation of a Temporary Autonomous Zone (TAZ) in the network and the relationship of the bodies of the components of TAZ with virtual tools. To achieve this overall objective, the researcher uses the theoretical foundation of: Hakim Bey (2001), Michel Foucault (1987), Clifford Geertz (1978), Maurice Merleau-Ponty (1999) and Donna J. Haraway (2000), discussing the concepts of culture, perception, power relations and bodies in contemporary society both online and offline. The research methodology is presented through netnography, theoretically based Hine (2000) and Kozinets (2002). In research there is a perceived need to integrate netnography with other instruments of data collection: mixed form and discourse analysis. The results achieved in the research are: the interactions between bodies/virtual tools have generated a model of stimulus-response in some subjects who participated in the experiment, not causing a deeper interactivity with the virtual tool. We also had bodies in which the interaction body/virtual tools transformed the relationship with the world and his own need for change, modifying his feeling to touch the world, its social context, offering their bodies for a freer contact and reviewing their existence in a space marked by discourses of power